2011
DOI: 10.1007/s12403-011-0040-0
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Genesis and Evolution of Water Quality Index (WQI) and Some Future Directions

Abstract: The concept of indexing water with a numerical value to express its quality, based on physical, chemical and biological measurements, was developed in 1965 by US based National Sanitation Foundation (NSF). In NSFWQI, the selection of parameters is based on Delphi method and these models were formulated in additive and multiplicative forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
218
0
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(238 citation statements)
references
References 67 publications
3
218
0
17
Order By: Relevance
“…There are many WQIs which had been developed and validated by researchers worldwide (Prasad and Kumari 2008;Reza and Singh 2010). The National Sanitation Foundation's Water Quality Index (NSF-WQI), the Canadian Council of Ministers of the Environment's Water Quality Index (CCME-WQI), the Oregon Water Quality Index (OWQI), and Heavy Metal Pollution Index (HPI) are well-known examples; the differences among WQIs are the statistical integration and interpretation of the resulting values (Alobaidy et al 2010;Lumb et al 2011;Abbasi and Abbasi 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There are many WQIs which had been developed and validated by researchers worldwide (Prasad and Kumari 2008;Reza and Singh 2010). The National Sanitation Foundation's Water Quality Index (NSF-WQI), the Canadian Council of Ministers of the Environment's Water Quality Index (CCME-WQI), the Oregon Water Quality Index (OWQI), and Heavy Metal Pollution Index (HPI) are well-known examples; the differences among WQIs are the statistical integration and interpretation of the resulting values (Alobaidy et al 2010;Lumb et al 2011;Abbasi and Abbasi 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There are a few studies that have reviewed the existing WQIs. Lumb et al (2011a) reviewed the conceptual frameworks of various WQI models developed from the 1960s till 2010 and presented the importance of various WQIs, the steps used in their formulation and their current uses. They also presented future directions and noted a need to develop a universally applicable WQI model that is flexible enough to cut across the available data for assessing the water quality for different uses.…”
Section: Environmental Monitoring and Assessment (2016) 188:58mentioning
confidence: 99%
“…In the course of using the index, it was found that the arithmetic formulation, although easy to understand and calculate, lacked sensitivity in terms of the effect a single bad parameter value would have on the WQI (Lumb et al 2011a). This led Brown et al (1973) to propose a variation of NSF WQI in which the multiplicative aggregation is used.…”
Section: D) Index Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lumb, Sharma y Bibeault [52] sostienen al respecto: "Todos los índices tienen una u otra limitación y la búsqueda de uno perfecto sigue siendo un desafío".…”
Section: Conclusionesunclassified